HUBUNGAN PENGETAHUAN PERAWAT TERHADAP PENANGANAN PASIEN GAWAT DARURAT PADA KASUS MIOKARD INFARK DI RUANG GAWAT DARURAT RUMAH SAKIT KEBONJATI BANDUNG - Ade Herawati; Enisah; Andi sukandi (LPPM Akper Kebonjati, 2023)
Knowledge is the result of knowing, and this occurs after people perceive a certain object (notoatmodjo, 2019). Indonesian hospital statistics for 2021 and 2022 show that other ischemic heart diseases account for the most cases of inpatient and outpatient treatment compared to other heart diseases. . The case fatality rate (CFR) of acute myocardial infarction is the highest compared to other heart diseases, namely 16.6% and 14.1% in 2018 and 2019, increasing from 10th (1999) and 14.1%. 9 (2019, 2020). Meanwhile, for inpatients, it is ranked 5th in 2021 and 2022, an increase from 8th (1st) and 7th (2022). The research results show that there is a relationship between knowledge and the role of nurses as implementers with a calculated rho value of 0.455 with a significance level of 0.033. With these results, it can be concluded that there is a relationship between knowledge and the role of nurses as implementers in treating patients with cardiovascular system disorders (Faridah, 2019; Nurses in the emergency room the emergency unit at Kebonjati Hospital Bandung mostly has a role in the adequate category as implementer in handling emergency patients with cardiovascular system disorders; there is a significant relationship between the level of knowledge of nurses and the role of nurses as implementers in handling emergency patients with cardiovascular system disorders; (p: 0.001 α: 0.05.)